Benchmarking best practices in youth associations in Malaysia: a case study - Tamam, Ezhar; Mohd Nor, Zanariah; Yaacob, Zamree (Universiti Putra Malaysia Press, 2005)
Acknowledging the significance of youth associations in capacity-building of Malaysian youths, a research was conducted to identify "best practices" in youth development work among the youth associations in Malaysia. This was a case study which analyzed a particular youth association that received the Best "Youth" Association national award in 2004. The data were gathered through in-depth interviews, document reviews and analysis, and observations. The data were analyzed using qualitative statistical methods. Nine key enablers - defined best practices that facilitate the desired progress and impact accomplished by the association - were identified: (1) environment that supports youth development needs and capacities, (2) sound, integrated need-based program that attracts members and the broader community, (3) strong support of the community, (4) strong linkage and partnership/collaborative approach with government and non-governmental agencies on youth work, (5) commitment of the members through their engagement in youth work, (6) committed and competent leaders and committee members who share objectives and directions, (7) reliable administration coupled with availability of supportive infrastructure, (8) continuous monitoring and evaluation of programs and activities, and (9) sustainable funding. Implications of the findings and future challenges were discussed.